2020
DOI: 10.1016/j.ejogrb.2020.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Adverse perinatal outcomes in 665,244 term and post-term deliveries—a Norwegian population-based study

Abstract: Objective: To assess the prevalence and risk of adverse perinatal outcomes in early-term (37 +0 -38 +6 weeks), full-term (39 +0 -40 +6 weeks), late-term (41 +0 -41 +6 weeks), and post-term (>42 +0 weeks) deliveries with spontaneous labor onset. Study design:A population-based cohort with data from the Medical Birth Registry Norway (MBRN) and Statistics Norway (SSB) was conducted. The study population consisted of 665,244 women with cephalic singleton live births at term or post-term with spontaneous labor onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…With regard to neonatal outcomes, the statically significant higher rates of the composite adverse neonatal outcome among the low annual volume group (10.9% vs. 10.3%, p<0.001%) was attributed to jaundice (4.1% vs. 3.7%, p<0.001%) and mechanical ventilation (0.3% vs. 0.2%, p<0.001). These rates were comparable with a large Norwegian population-based study that assessed adverse perinatal outcomes in 665,244 term and post-term deliveries 20 Even with the statistically significant difference in the mechanical ventilation rate (0.3% vs. 0.2%) no other statistically significant difference in Apgar scores, neonatal asphyxia and NICU Admissions rates were determined.…”
Section: Discussionsupporting
confidence: 76%
“…With regard to neonatal outcomes, the statically significant higher rates of the composite adverse neonatal outcome among the low annual volume group (10.9% vs. 10.3%, p<0.001%) was attributed to jaundice (4.1% vs. 3.7%, p<0.001%) and mechanical ventilation (0.3% vs. 0.2%, p<0.001). These rates were comparable with a large Norwegian population-based study that assessed adverse perinatal outcomes in 665,244 term and post-term deliveries 20 Even with the statistically significant difference in the mechanical ventilation rate (0.3% vs. 0.2%) no other statistically significant difference in Apgar scores, neonatal asphyxia and NICU Admissions rates were determined.…”
Section: Discussionsupporting
confidence: 76%
“…A Norwegian population‐based study showed that deliveries at early term were associated with an increased number of neonatal jaundice, polyhydramnios, small for gestational age, respiratory support and neonatal intensive care unit admission compared with deliveries at 39 to 43 weeks. Poor Apgar scores and requirement for antibiotic treatment were higher in early‐term and post‐term new‐borns while meconium‐stained liquor and new‐born birth injuries increased with increasing gestational age 26 . The above suggest that full‐term delivery is probably best for short‐term infant outcomes.…”
Section: Discussionmentioning
confidence: 92%
“…The first large study to demonstrate this, published in 2012, used a cohort of 18,818 infants and found that individuals born between 37 and 38 weeks gestational age had a higher risk of adverse health and developmental outcomes at age 3 compared to those born between 39 and 41 weeks gestational age (Boyle et al, 2012). Subsequent studies have linked other adversities with early term birth, including higher risks of neonatal (Murzakanova et al, 2020) and later childhood illness (Coathup et al, 2020) and less favourable neurodevelopmental outcomes in early life (Hua et al, 2019; Rose et al, 2013).…”
Section: Introductionmentioning
confidence: 99%